Nosocomial acute gastroenteritis outbreak caused by an equine-like G3P[8] DS-1-like rotavirus and GII.4 Sydney[P16] norovirus at a pediatric hospital in Rio de Janeiro, Brazil, 2019 - Meylin B. Gutierrez; Mirza Rocha de Figueiredo; Alexandre Madi Fialho; Carina Pacheco Cantelli; Marize Pereira Miagostovich; Tulio Machado Fumian (Taylor & Francis Group, 2021)
Worldwide, rotavirus (RVA) and norovirus are considered major etiological agents of acute gastroenteritis (AGE) in pediatric population admitted to hospitals. This study describes the investigation of nosocomial infections caused by emergent RVA and norovirus strains reported at a pediatric hospital in southern Brazil in May 2019. This outbreak affected 30 people among children and adults. Nine stool samples (eight children and one nurse) were obtained and analyzed by RT-qPCR to detect and quantify RVA and norovirus. Positive samples were genotyped by sequencing and subjected to phylogenetic analysis. We detected RVA in 44.4% (4/9) and norovirus in 55.5% (5/9) at high viral loads, ranging from 3.5 × 107 to 6.1 × 107 and 3.2 × 102 to 3.2 × 109 genome copies/g of stool, respectively. Co-infections were not observed. RVA VP4 and VP7 gene sequencing in combination with polyacrylamide gel electrophoresis identified the circulation of equine-like G3P[8] DS-1-like, and the partial sequencing of the other nine genes revealed that strains possessed I2-R2-C2-M2-A2-N1-T2-E2-H2 genotype background. The emergent recombinant norovirus variant, GII.4 Sydney[P16], was identified by ORF1-2 sequencing. Active surveillance and effective prevention measures should be constantly reinforced to avoid the spread of nosocomial viral infections into hospitals, which could severely affect pediatric patients admitted with underlying health conditions.